2013
DOI: 10.4269/ajtmh.13-0112
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of Onchocerca volvulus Transmission in the Abu Hamed Focus, Sudan

Abstract: Abstract. Abu Hamed, Sudan, the northernmost location of onchocerciasis in the world, began community-directed treatment with ivermectin (CDTI) in 1998, with annual treatments enhanced to semiannual in 2007. We assessed the status of the parasite transmission in 2011 entomologically, parasitologically, and serologically. O-150 pool screening showed no parasite DNA in 17,537 black flies collected in 2011 (95% confidence interval upper limit [95% CI UL] = 0.023). Skin microfilariae, nodules, and signs of skin di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 27 publications
3
65
1
Order By: Relevance
“…The number of samples collected and screened in this study complies with the limits set by WHO guidelines of at least 6,000 black flies and 2,000 blood spots per transmission zone. 16 Previously we reported the first evidence of interruption of O. volvulus transmission in Africa achieved with annual and semiannual ivermectin mass treatment alone in Abu Hamed in 2012, 14 and now provide evidence for the first elimination of onchocerciasis after PTS in Africa following the new WHO guidelines for verification of onchocerciasis transmission interruption and elimination 16 ; these guidelines are based on the successes in South America. [9][10][11] Our data meets the major recommendation of < 1% upper limit 95% CI of infection where no black flies screened by the O-150 PCR assay are infected, as well as the upper limit of the 95% CI of 0.1% for the prevalence of infection in children ≤ 10 years of age.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The number of samples collected and screened in this study complies with the limits set by WHO guidelines of at least 6,000 black flies and 2,000 blood spots per transmission zone. 16 Previously we reported the first evidence of interruption of O. volvulus transmission in Africa achieved with annual and semiannual ivermectin mass treatment alone in Abu Hamed in 2012, 14 and now provide evidence for the first elimination of onchocerciasis after PTS in Africa following the new WHO guidelines for verification of onchocerciasis transmission interruption and elimination 16 ; these guidelines are based on the successes in South America. [9][10][11] Our data meets the major recommendation of < 1% upper limit 95% CI of infection where no black flies screened by the O-150 PCR assay are infected, as well as the upper limit of the 95% CI of 0.1% for the prevalence of infection in children ≤ 10 years of age.…”
mentioning
confidence: 99%
“…In this assessment, no infection was found in > 17,000 black flies screened by O-150 PCR, no antibodies to Ov16 antigen in 6,756 children ≤ 10 years of age, and no signs of infection in 536 adult individuals from seven communities within the focus. 14 This assessment indicated that the disease transmission has been interrupted in Abu Hamed based on the WHO 2001 guidelines for interruption of onchocerciasis transmission. 11 Review of these findings prompted the government of Sudan to declare interruption of the parasite transmission, halting mass treatment activities, and beginning a 3-year posttreatment surveillance (PTS) phase in May 2012 ( Figure 1B).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5 However, recent data have suggested that this is not the case, and that long-term community wide distribution of ivermectin may be capable of eliminating onchocerciasis in at least some foci in Africa. [6][7][8][9][10] This discovery has resulted in a refocusing of the international community from an emphasis on control of onchocerciasis in Africa toward an emphasis upon possible elimination. 11,12 Monitoring and evaluation activities are especially necessary in elimination efforts to document the effectiveness of program operations and eventually in showing that transmission had been interrupted.…”
Section: Introductionmentioning
confidence: 99%